1997
DOI: 10.1007/pl00005658
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-sensory modality matching in children with hand-eye co-ordination problems

Abstract: Inter- and intra-sensory modality matching by 8-year-old children diagnosed as having hand-eye co-ordination problems (HECP) and by a control group of children without such problems were tested using a target-location and pointing task. The task required the children to locate target pins visually (seen target), with the hand (felt target) or in combination (felt and seen target), while pointing to the located target was always carried out without vision. The most striking finding, for both the control and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 31 publications
5
53
0
1
Order By: Relevance
“…As discussed above, a number of authors have focused on cerebellar dysfunction in this context, and interpreted their findings in the light of the cerebellar timing hypothesis (Ivry and Diener, 1991;Ivry and Keele, 1989;Keele et al, 1987Keele et al, , 1985. However, given the fact that temporally dependent bimanual co-ordination problems have been observed in co-occurrence with bimanual co-ordination tasks that are independent of temporal constraints (Sigmundsson, 1989;Sigmundsson et al, 1997aSigmundsson et al, , b, 1999, the cerebellar timing hypothesis would not seem to hold for all kinds of bimanual co-ordination. The same kind of bimanual co-ordination problems (screwing nuts onto bolts and threading beads) to those observed in the present study, have been found in a group of 8-year-old motor impaired children with particular problems in hand-eye co-ordination .…”
Section: Inter/intra Hemispheric Deficitmentioning
confidence: 96%
See 1 more Smart Citation
“…As discussed above, a number of authors have focused on cerebellar dysfunction in this context, and interpreted their findings in the light of the cerebellar timing hypothesis (Ivry and Diener, 1991;Ivry and Keele, 1989;Keele et al, 1987Keele et al, , 1985. However, given the fact that temporally dependent bimanual co-ordination problems have been observed in co-occurrence with bimanual co-ordination tasks that are independent of temporal constraints (Sigmundsson, 1989;Sigmundsson et al, 1997aSigmundsson et al, , b, 1999, the cerebellar timing hypothesis would not seem to hold for all kinds of bimanual co-ordination. The same kind of bimanual co-ordination problems (screwing nuts onto bolts and threading beads) to those observed in the present study, have been found in a group of 8-year-old motor impaired children with particular problems in hand-eye co-ordination .…”
Section: Inter/intra Hemispheric Deficitmentioning
confidence: 96%
“…Sigmundsson and his colleagues Sigmundsson et al, 1997aSigmundsson et al, , b, 1999, for example, signal possible inter-hemispheric information transfer problems while other authors have focused on cerebellar mediation. In the latter context, Ivry and his colleagues (Ivry and Diener, 1991;Ivry and Keele, 1989;Keele et al 1987;Keele et al, 1985) have suggested the possibility of a breakdown in the control of the temporal coupling of signals.…”
Section: Introductionmentioning
confidence: 96%
“…But the disability has also been related to perception, such as a deficit in the mapping of visual and proprioceptive information [8,9], difficulties in visuomotor integration [10] and abnormalities in the execution of movements without perceptual component [11]. These findings seem to suggest that DCD is a fairly generalized problem, affecting movement, as well as perception.…”
Section: Introductionmentioning
confidence: 95%
“…Children with DCD showed more problems with the processing of proprioceptive information than typically developing children in tasks that involved locating targets under a table-top with one hand while attempting to match the position of the target with the other on the table-top. In addition, children with DCD demonstrate defi cits in the ability to integrate visual and kinesthetic information Sigmundsson, Ingvaldsen, & Whiting, 1997). However, one can argue that because of the diffi culty to assess such defi cits in a way that excludes pure motor control problems, it might be inappropriate to make assumptions about the functioning of the perceptual system (Wilson & McKenzie 1998).…”
mentioning
confidence: 99%